2005
DOI: 10.1152/ajpregu.00126.2005
|View full text |Cite
|
Sign up to set email alerts
|

Daily expression of clock genes in whole blood cells in healthy subjects and a patient with circadian rhythm sleep disorder

Abstract: . Daily expression of clock genes in whole blood cells in healthy subjects and a patient with circadian rhythm sleep disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 45 publications
7
42
1
Order By: Relevance
“…4a). The highest hPer1 transcription in peripheral blood was previously observed in healthy human subjects at times experienced as morning [10,11,13,14]. The current result was consistent with these previous reports.…”
Section: Levels Of Plasma Noradrenalinesupporting
confidence: 93%
See 1 more Smart Citation
“…4a). The highest hPer1 transcription in peripheral blood was previously observed in healthy human subjects at times experienced as morning [10,11,13,14]. The current result was consistent with these previous reports.…”
Section: Levels Of Plasma Noradrenalinesupporting
confidence: 93%
“…Although a detailed molecular mechanism of the circadian oscillator has been revealed in rodents that are nocturnally active, there have been few studies in diurnally active humans. Recently, human peripheral blood cells have been used for representative estimations of the mRNA expression of clock genes in other peripheral tissues [10][11][12][13][14].…”
mentioning
confidence: 99%
“…1b-e, the mRNA expression of BMAL1, PER1, PER2 and PER3 exhibited slight but significant 24 h rhythmicity (χ 2 =12.9, p<0.01 for BMAL1; χ 2 =22.9, p<0.001 for PER1; χ 2 =22.0, p<0.001 for PER2; χ 2 =25.0, p<0.001 for PER3; Friedman test to evaluate rhythmicity). Similarly to previous reports [6][7][8]21], the levels of PER1, PER2 and PER3 peaked in the early morning and dropped to a trough level in the evening. On the other hand, the mRNA levels of CLOCK, CRY1 (Fig.…”
Section: Study 1 Because Biological Clock Function In Leucocytes Issupporting
confidence: 87%
“…Recent studies revealed that the circadian clock system consists essentially of a set of clock genes [1,2]. The circadian clock resides in the hypothalamic suprachiasmatic nucleus (SCN), which is recognised as being the master clock, and the same clock exists also in almost all peripheral tissues, including liver, heart, kidney [3][4][5] and leucocytes [6][7][8]. Although the SCN is not essential for driving peripheral oscillations, it appears to coordinate peripheral clocks [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, human PBMCs have been used as a surrogate to estimate likely mRNA expression of clock genes in other peripheral tissues (16 -18). The greatest hPer1 transcription was observed in human subjects during the morning hours (17,18,31).…”
Section: Glucocorticoid Induces Human Period1 Mrnamentioning
confidence: 96%